War of the realms: new agents of atlas ebook - Pak, Greg (War of the Realms: New Agents of Atlas (2019)., 2019)
Collects War Of The Realms: New Agents Of Atlas #1-4. A new band of heroes unites to defend the Pacific Rim! As Sindr and her legions of Fire Demons march on Asia, can Amadeus Cho reassemble his ragtag "Protectors" — Shang-Chi, Silk and Jimmy Woo — to once again save Earth from an alien invasion? Where is Kamala Khan? And just who are Crescent, Io and Luna Snow? Prepare to meet Marvel's newest heroes from China — Aero and Sword Master — and the mysterious new Filipina heroine named Wave! Together, they are all that stands between the Queen of Cinders and her ultimate goal: to melt the polar ice caps and turn all of Midgard into a sweltering new Muspelheim!